Mapping Global Trends of Employee Relations and Innovation: A Human Capital-Based Bibliometric Analysis: English - Hasanah, Nurul; Ariani, Gusti Meinar Girda; Yulianti, Farida; Syahrani; Wicaksono, Teguh (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study aims to systematically map global research trends concerning employee relations as a key driver of innovative work behavior through the lens of human capital. Responding to the fragmentation of previous studies and the lack of an integrative perspective, this research employs a bibliometric analysis approach to uncover conceptual structures, thematic clusters, and intellectual linkages in this evolving field. A total of 142 peer-reviewed articles published between 2024 and 2025 were retrieved from Scopus and Google Scholar databases using a targeted keyword string. The data were refined using the PRISMA protocol and analyzed with VOSviewer to generate network, overlay, density, and co-author collaboration visualizations. The findings reveal four main clusters: internal organizational performance, antecedents and structural barriers, methodological approaches, and external innovation drivers such as digital transformation and entrepreneurship. Core concepts including human capital, employee behavior, and innovation were central in the co-occurrence networks, while emerging themes such as governance, resilience, and collaboration indicated underexplored areas. The co-author collaboration map highlights regional fragmentation and limited cross-institutional partnerships, suggests opportunities for global integration. These findings emphasize the theoretical need to reconceptualize employee relations within dynamic innovation ecosystems and offer practical insights for HR strategists to develop relational practices that effectively harness human capital. This study contributes to the literature by offering a holistic, data-driven perspective on how employee relations are positioned in advancing workplace innovation in the digital age.